Growth Performance of Clown Anemonefish (Amphiprion ocellaris) in Maluku at Optimum Salinity - Fitrinawati, Henny; Syahailatua, Diana Yulanda; Utami, Endang Sri (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2024)
Clown anemonefish (Amphiprion ocellaris) is one of the most popular ornamental coral reefs. The marine ornamental fish trade has increased fishing pressure. It has a considerable impact on the clown anemonefish's declining population. The ability of each fish species to tolerate the salinity is a vital consideration in aquaculture marine organisms as it gives information on primary environmental necessities. This study aimed to analyze the clown anemonefish growth performance by modifying different salinity levels through survival rate, specific growth rate, and feed conversion ratio parameters. The experiment was conducted with a Completely Randomized Design (CRD) to investigate the effect of salinity on clown anemonefish growth performance with six treatments (24, 26, 28, 30, 32, and 35 ppt) and three replications. Water quality parameters in this study observed include pH, temperature, and dissolved oxygen. The clown anemonefish reared with six different salinity treatments for 30 days showed that there was a significantly different effect on SGR (p value = 0.007) but no significant differences in FCR (p value = 0.189) and survival rates (p value = 0.458). The considerable effect of salinity on specific growth rates explains that the amount of energy used in the osmoregulation process disrupts a portion of growth energy. The optimal growth performance of clown anemonefish was in a 24 ppt salinity treatment, accompanied by other water quality parameters such as temperature, dissolved oxygen, and pH, which ranged from 26.5 – 32oC; 4.9 - 5.6 ppm; and 7.9 - 8.2, respectively.Keywords: Amphiprion ocellaris, clown anemonefish, growth performance, salinity